2019
DOI: 10.1016/j.paerosci.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

A survey of icephobic coatings and their potential use in a hybrid coating/active ice protection system for aerospace applications

Abstract: Icephobic coatings for aircraft and other surfaces subjected to ice accretion have generated great interest in the past two decades, due to the advancement of nanomaterials, coating fabrication methods, biomimetics, and a more in-depth understanding of ice nucleation and ice adhesion. Icephobic coatings have demonstrated the ability to repel water droplets, delay ice nucleation and significantly reduce ice adhesion. Despite these ongoing research activities and promising results, the findings reported hereafte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(111 citation statements)
references
References 105 publications
0
111
0
Order By: Relevance
“…The challenges and limitations of the synthesis of stable superhydrophobic coatings were also included and discussed. One of the main advantages of superhydrophobic coatings is that these types of materials may include other properties, such as anti-fouling [276], anti-icing [309] and bio-corrosion [231]. According to a review published by Montemor [231] in 2014, several reported encapsulation-based strategies seem to be promising; however, only a few studies were reported which validated the proposed strategies regarding the corrosion protection behavior [310][311][312].…”
Section: Coatings With Superhydrophobic Functionmentioning
confidence: 99%
“…The challenges and limitations of the synthesis of stable superhydrophobic coatings were also included and discussed. One of the main advantages of superhydrophobic coatings is that these types of materials may include other properties, such as anti-fouling [276], anti-icing [309] and bio-corrosion [231]. According to a review published by Montemor [231] in 2014, several reported encapsulation-based strategies seem to be promising; however, only a few studies were reported which validated the proposed strategies regarding the corrosion protection behavior [310][311][312].…”
Section: Coatings With Superhydrophobic Functionmentioning
confidence: 99%
“…An objective and bias-free analysis of the state-of-the-art in anti-icing materials employing the virtue of water repulsion, proffers that functional material alone may not be able to ensure the desired efficacy for aircraft or wind turbine de-icing operations [144,145]. Instead, combining an icephobic coating with electric heating emerges as a convenient option for icing mitigation in atmospheric conditions [144][145][146][147][148][149][150]. The focus in these hybrid systems is on the reduced power consumption up to 50%-90% both in glaze and rime ice regimes [145,148].…”
Section: Novel Hybrid Anti-icing Systemsmentioning
confidence: 99%
“…In turn, the ice accretion in the hydrophobic surface area is low, due to the fast runback speed of the impacting water droplets, whilst thermal energy is exploited predominantly for eliminating the attached ice at the leading edge [145]. Even though the hybrid strategy is promising for real-life performance, for the case of electromechanical de-icing is of utmost importance to choose a coating that would not adversely affect the stress generation, as the latter defines the coupling between the source and the ice-substrate interface [144].…”
Section: Novel Hybrid Anti-icing Systemsmentioning
confidence: 99%
“…They suggested that the anti-icing surfaces can not only delay the freezing time, but also can reduce the freezing point [105]. Huang et al also summarized the anti-icing coating for aerospace application, which demonstrated the ability to repel water droplets, delay ice nucleation, and significantly reduce ice adhesion [106]. Ruan et al prepared rough alumina surfaces with a large WCA of 157.6 • ; this surface can delay the icing time and reduce the freezing temperature to 65 min and −8.3 • C, respectively [107].…”
Section: Structural Steelsmentioning
confidence: 99%